The Effect of Family Communication Patterns on Goal Orientation in Students of Asaluyeh Universities - Parvaneh Doodman (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2017)
Background and Objectives: The goal orientation theory is one of the newest approaches, which has been introduced to the field of motivation psychology in the recent three decades. In the present research, the prediction level of different types of goal orientation, including dominance-approach, dominance-avoidance, performance-approach, and performance-avoidance, was investigated using different dimensions of family communication patterns, such as dialogue and conformity domains.   Methods: This descriptive-correlational study, was conducted on 300 students (150 females and 150 males) from different universities in asaluyeh city. Elliot and McGregor's Goal Orientation Scale was used to assess goal orientation, and Koerner and Fitzpatrick revised scale (2002) was used to assess dimensions of family communication patterns. The predictive value of each type of goal orientation of two dimensions of dialogue and conformity of family communication patterns, was evaluated using simultaneous multiple regression analysis.   Results: In this study, the mean scores of communication patterns of family dialogue and conformity, were obtained 39.66±10.13 and 24.85±9.07. respectively. Also, the mean scores in orientations of dominance-approach, dominance-avoidance, performance-approach, and performance-avoidance, were 15.34±4.15, 12.79±3.87, 14.35±4.149 and 13.89±3.495, respectively. Family dialogue predicted the goal orientations of dominance-approach, performance-approach, and performance-avoidance; and family conformity predicted dominance-avoidance, performance-approach, and performance-avoidance.    Conclusion: Findings of this research indicated that improvement of family dialogue is predictive of the goals of dominance- and performance-approach in children; whereas, emphasis on family conformity predicts the goals avoidance- and performance-approach.